Kafes kodlamalı hızlı frekans kaydırmalı anahtarlama tekniğinin otomatik yineleme istemeli sistemlere uyarlanması - Durak, Taner (Fen Bilimleri Enstitüsü, 1993)
Bu tez çalışmasında, kodlama ve modülasyon işlemlerinin bir bütün olarak ele alındığı kafes kodlamalı Hızlı Frekans Kaydırmalı Anahtar lama (Fast Frequency Shift Keying, FFSK> modülasyonu, iletişim sistemlerinde hata kontrolü için kullanılan bir yöntem olan Otomatik Yineleme istemeli f. Automatic Repeat Request, ARQ> tekniğine uygulanmıştır. Tene! yapı oluşturulduktan sonra, alıcı tarafta bellek kullanılması ve kod sözcüğünün ilk iletiminde hata serildiğin de verici tarafından aynı sözcüğün "m" kez ard arda iletilmesi gibi iyileştirmeler sisteme ilave edilerek, başarımın arttırılması yoluna gidilmiştir. Oluşturulan sistemlerin Gauss gürültülü ve Rayleigh genlik sünümlemeli kanallardaki iş çıkarma yetenekleri ve bit hata olasılık üst sınırları analitik yöntemlerle incelendiği gibi oluşturulan bir benzetim modeli yardımıyla da değerlendirilmiştir.

In this thesis, trellis coded fast frequency shift keying (FFSK) technique is introduced for modula tion operation in automatic-repeat-request (ARQ) schemes in order to improve their throughput performances. The performance of the proposed system is investigated in noisy and fading environment by both analytical and simulation approaches. On the other hand, some modifica tions like the m>l times retransmission of the codeword detected in error or the use of a memory in the receiver are also considered. There are two basic types of error-control schemes in data transmission systems: the forward-error control . Each block of 3 information symbols coming out of the source is encoded in a codeword g of a code C(6,3). g is G symbols long. Code C is able to correct 2 = 26_3=8 errors and to detect 2n-2k=26 -23=56 errors. C<6, 3) is used only to detect errors in the receiver which sends a negative acknowledgement for each erroneously decoded codeword. R=l/2 trellis coded FFSK modulator is made up of a good combination of R=l/2 convolutional code and FFSK modulation. Each coming symbol from the block encoder, is translated into 2 FFSK signals. Each signal has a duration of T sec and this is referred as the modulation interval. As a result of FFSK modulation, there is a phase continuity at signal transitions. At the receiver part, we use soft-decision Viterbi decoder, so that demodulation and decoding operations are considered together. The Viterbi algorithm decides after each 12 T sec. long observation interval, and delivers the corresponding received binary sequence of 6 bits long to the (6,3) block decoder. Then, the received sequence is compared to the codewords of the linear block code C<6, 3) If the received sequence is a codeword of the code C(6, 3) then, the receiver sends a positive acknowledgement to the transmitter through a noiseless feedback channel and the information bits are delivered to the user. On the other hand, if the received vector is not a codeword of the code C(6, 3) then, the receiver sends a negative acknowledgement to the transmitter. The transmitter then stops sending new codewords and retransmits this codeword, detected in error. Retransmissions continue -x- until the transmitter receives positive acknowledgement for that codeword. Many modifications have been introduced in order to improve the performance of ARQ techniques. An interesting approach is the introduction of a memory in the decoding operation. In this case, the received vectors, also those detected in error, are retained in order to facilitate the correct decoding of the transmitted codeword. In some ARQ schemes, a codeword detected in error is retransmitted m times consecutively in order to increase the throughput under high error rate conditions. In the second section, the three basic ARQ techniques, stop and wait, go back-N, and selective- repeat, and their throughput analysis are presented. The third section is destinated to the FFSK modulation technique which is interesting especially for earth-satellite communications with its constant envelope continuous phase and spectral efficiency characteritics. The integration of coding and modulation operations for ARQ schemes are considered in section 4. Different approaches given in the literature are compared. In the fifth section, the ARQ scheme using trellis coded FFSK modulation is presented and its throughput and error performances over additive Gaussian noisy and amplitude fading channels are analyzed. The bit error probability upper bounds for 2 and 4 state FFSK encoders are obtained based on the transfer approach. On the other hand, a simulation model for the proposed ARQ scheme is used to obtain its throughput with respect to the signal-to-noise ratio in noisy and fading environment. The last section is destinated to a conclusion of the obtained results.
The Application of trellis coded fast frequency shift keying modulation to the automatic repeat request systems
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1993
Keywords: Anahtarlama; Frekans kayması; Kafes kodlama; Otomatik sistemler; Switching; Frequency shift; Trellis coding; Automatic systems